2018
DOI: 10.1016/j.scitotenv.2018.05.277
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm colonization of metamorphic lithotypes of a renaissance cathedral exposed to urban atmosphere

Abstract: Stone architectural heritage exposed outdoor represents a challenging habitat for biological growths; nevertheless, biocolonization on heritage structure is ubiquitous and represents a major mechanism of alteration. However, the identification of specific microorganisms with known reactivity towards the stone substrate does not necessarily imply that a biodeterioration process is in progress and, in specific conditions, bioprotection effects have been highlighted as a result of colonization. The main objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 49 publications
1
26
0
1
Order By: Relevance
“…Microscope observations and molecular analysis showed that Cyanobacteria, Proteobacteria and Actinobacteria were the main bacteria present on the untreated Candoglia marble. The microscopic investigations did not show the presence of hyphae and spores that might be correlated to the presence of fungi as also reported in our previous investigation [1]. Alphaproteobacteria are often the predominant taxa on stone buildings [37], and in the Altamira cave they have been found to be the most metabolically active class of the Proteobacteria [38].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Microscope observations and molecular analysis showed that Cyanobacteria, Proteobacteria and Actinobacteria were the main bacteria present on the untreated Candoglia marble. The microscopic investigations did not show the presence of hyphae and spores that might be correlated to the presence of fungi as also reported in our previous investigation [1]. Alphaproteobacteria are often the predominant taxa on stone buildings [37], and in the Altamira cave they have been found to be the most metabolically active class of the Proteobacteria [38].…”
Section: Discussionsupporting
confidence: 77%
“…In previous work by our team [1], we proved that despite the massive presence of biofilms causing aesthetic alteration to the façade of Monza Cathedral, the biocolonization was not a primary damaging factor if compared to chemical-physical deterioration due to the aggressive polluted atmosphere. Nonetheless, the conservators of the Monza Cathedral have tried to remove the sessile dwelling microorganisms to reduce discoloration based on their previous experiences in similar cases.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Built Heritage is subjected to deterioration caused by a number of factors, environmental and anthropogenic as well. Among the first type, blackening of surfaces due to carbon particles accumulation, nitrogen oxides action and bacteria-induced growing of microorganisms may be cited (Brimblecombe and Grossi, 2005;Gulotta et al 2018;Pozo-Antonio et al 2019;Vidal et al 2019) The water access to the inner part of the building materials might be commented as another way of deterioration (Brai et al, 2007;Piuzzi et al 2018). As a matter of fact, water can penetrate into the materials giving rise to soluble salts dissolution, efflorescences and the breaking of the materials due to freezing-thawing cycles.…”
Section: Introductionmentioning
confidence: 99%
“…This included optical and scanning electron microscopy, Fourier-transformed infrared spectroscopy, and X-ray diffraction analysis. Specific diagnostic techniques were also employed to analyze the extensive biocolonization affecting the crowning element of the façade, to better understand the potential damaging role of the biofilms [40]. This last phase of the preliminary knowledge of the site features highlighted, as expected, that the deposition of particulate matter and black crust formation were major damage mechanisms of the stone elements partially sheltered from the rain runoff.…”
Section: Phase 1: Condition Survey and Characterization Of Materialsmentioning
confidence: 97%